(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
Abstract: In this article, the main goal of the reforms implemented in Uzbekistan is to create decent living conditions for every citizen of our nation. This serves to make every citizen, regardless of nationality, understand the nature of the reforms implemented in our country and become an active participant in it. In this, the national idea is promoted.